Pengaruh Kualitas Produk dan Harga terhadap Kepuasan Konsumen pada Rumah Makan Serba Nikmat di Kota Palopo - Harmi Ningsi; Najwa Artika Zahra D; Febriyani.P; Fauzan Riski; Nasruddin Nasruddin; Andi Dewi Angreyani (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to determine the influence of product quality and price on customer satisfaction at Rumah Makan Serba Nikmat in Palopo City. In an increasingly competitive culinary business environment, business owners are required to continuously improve product quality and pricing strategies to maintain customer loyalty. Customer satisfaction serves as a crucial indicator of business success, as satisfied customers are more likely to make repeat purchases and recommend the restaurant to others.The research adopts a quantitative method using a descriptive and associative approach. Primary data were collected through questionnaires distributed to 70 respondents who were selected incidentally from the restaurant's customer base. The data were analyzed using multiple linear regression to examine both the simultaneous and partial effects of the independent variables (product quality and price) on the dependent variable (customer satisfaction). The results of the study reveal that product quality and price simultaneously have a significant effect on customer satisfaction, with an F-value of 22.207 and a significance level of 0.000, which is less than 0.05. Partially, product quality has a significant effect on customer satisfaction, with a t-value of 4.311. Likewise, price also shows a significant effect with a t-value of 2.204. The coefficient of determination (R²) is 0.399, indicating that 39.9% of the variation in customer satisfaction can be explained by product quality and price, while the remaining 60.1% is influenced by other factors not examined in this study.Based on these findings, it is recommended that Rumah Makan Serba Nikmat continue to improve the quality of its products by focusing on taste, presentation, hygiene, and consistency. In addition, maintaining competitive and affordable pricing strategies that align with customer expectations is essential to ensure sustainable customer satisfaction. Enhancing both of these factors will contribute to building stronger customer loyalty and supporting long-term business success in the competitive culinary industry.